A let-7-to-miR-125 MicroRNA Switch Regulates Neuronal Integrity and Lifespan in Drosophila. - Geetanjali Chawla; Padmini Deosthale; Sue Childress; Yen-Chi Wu; Nicholas S Sokol (PLoS Genetics)
Messenger RNAs (mRNAs) often contain binding sites for multiple, different microRNAs (miRNAs). However, the biological significance of this feature is unclear, since such co-targeting miRNAs could function coordinately, independently, or redundantly with one another. Here, we show that two co-transcribed Drosophila miRNAs, let-7 and miR-125, non-redundantly regulate a common target, the transcription factor Chronologically Inappropriate Morphogenesis (Chinmo). We first characterize novel adult phenotypes associated with loss of both let-7 and miR-125, which are derived from a common, polycistronic transcript that also encodes a third miRNA, miR-100. Consistent with the coordinate upregulation of all three miRNAs in aging flies, these phenotypes include brain degeneration and shortened lifespan. However, transgenic rescue analysis reveal separable roles for these miRNAs: adult miR-125 but not let-7 mutant phenotypes are associated with ectopic Chinmo expression in adult brains and are suppressed by chinmo reduction. In contrast, let-7 is predominantly responsible for regulating chinmo during nervous system formation. These results indicate that let-7 and miR-125 function during two distinct stages, development and adulthood, rather than acting at the same time. These different activities are facilitated by an increased rate of processing of let-7 during development and a lower rate of decay of the accumulated miR-125 in the adult nervous system. Thus, this work not only establishes a key role for the highly conserved miR-125 in aging. It also demonstrates that two co-transcribed miRNAs function independently during distinct stages to regulate a common target, raising the possibility that such biphasic control may be a general feature of clustered miRNAs.